Integrated Behavioral-Health and Social-Needs Care Coordination Following Nonfatal Firearm Injury: A Critical Narrative Review and Framework for Longitudinal Recovery - Kassim Nimotalai Olusola; Deborah Ave Okon; Atoyebi Oluwapelumi Diadem (Journal of Life Science and Public Health, 2026)
Survival after a nonfatal firearm injury does not mark the end of the health consequences of that injury. A substantial share of survivors experience persistent post-traumatic stress, depression, chronic pain, and disrupted housing, employment, and transportation, and these domains interact to shape recovery. This narrative review synthesizes evidence on behavioral-health and social-needs care following nonfatal firearm injury, critically examines why conventional post-trauma systems are structurally poorly suited to this phase of care, and evaluates the evidence for behavioral-health screening, social-needs intervention, and hospital-based violence intervention programs (HVIPs). Across intervention types, evidence of improved service engagement is more consistent than evidence of improved long-term clinical or safety outcomes, and few studies test integration of these components as a single coordinated pathway. Building on recurring mechanisms identified in the literature, this review proposes the Integrated Firearm Injury Recovery and Care Coordination (IFIR-CC) framework. This testable conceptual model links acute stabilization to needs assessment, individualized planning, multidisciplinary coordination, closed-loop follow-up, and secondary prevention. This review contributes a testable conceptual model that synthesizes recurring mechanisms from the literature and provides a research agenda for evaluating integrated care coordination, organizing post-injury care around six interconnected, non-linear functions: acute stabilization; comprehensive needs assessment; individualized recovery planning; multidisciplinary coordination with clearly defined responsibilities; closed-loop longitudinal follow-up; and recovery, reintegration, and secondary prevention. The review concludes with a research agenda that prioritizes longitudinal outcome measurement, comparative effectiveness evaluation of delivery models, and equity-focused implementation research.